Pengaruh Leverage, Likuiditas, dan Ukuran Perusahaan Terhadap Profitabilitas Pada Perusahaan Textile dan Garment Yang Go Public Di Bursa Efek Indonesia - Nuraini, Faradibah Desy; Suwaidi, Rahman Amrullah (Universitas muhammadiyah palembang, 2022)
To get the maximum profit, the company must be able to compete with other companies and must improve the company’s performance in order to maximize the profit received. The aim of this study is to determine the effect of leverage, liquidity, and firm size on profitability. The dependent variable in this research is profitability and the independent variables are leverage, liquidity, and firm size. This research was conducted at textile and garment companies that went public on the Indonesia Stock Exchange during the 2016-2019 period. And with a total of 19 companies or population in this research. The sample in this study were 9 companies with a total of 36 data obtained using purposive sampling method and data analysis using multiple linear regression. The result of this study state that leverage has a negative and significant effect on profitability, liquidity has a positive and significant effect on profitability, and firm size has no and not significant effect on profitability.